Mildly Infuriating

Calculus Level 4

n = 1 n 2 2 n = ? \sum _{ n=1 }^{ \infty }{ \frac { { n }^{ 2 } }{ { 2 }^{ n } } } = \ ?

Too easy? Try a more brutal related question .


The answer is 6.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

4 solutions

Discussions for this problem are now closed

Let S = n = 1 n 2 2 n S = \displaystyle \sum_{n=1}^\infty \frac{n^{2}}{2^{n}} . Then:

S = 1 2 2 1 + 2 2 2 2 + 3 2 2 3 + + k 2 2 k + S = \frac{1^{2}}{2^{1}} + \frac{2^{2}}{2^{2}} + \frac{3^{2}}{2^{3}} + \ldots + \frac{k^{2}}{2^{k}} + \ldots

Multiply both sides by two:

2 S = 1 2 2 0 + 2 2 2 1 + 3 2 2 2 + + ( k + 1 ) 2 2 k + 2S = \frac{1^{2}}{2^{0}} + \frac{2^{2}}{2^{1}} + \frac{3^{2}}{2^{2}} + \ldots + \frac{(k + 1)^{2}}{2^{k}} + \ldots

Subtracting S S from 2 S 2S :

2 S S = 1 + 3 2 + 5 2 2 + 7 2 3 + + 2 k + 1 2 k + 2S - S = 1 + \frac{3}{2} + \frac{5}{2^{2}} + \frac{7}{2^{3}} + \ldots + \frac{2k + 1}{2^{k}} + \ldots

Then: S = i = 0 2 i + 1 2 i S = \displaystyle \sum_{i=0}^\infty \frac{2i + 1}{2^{i}}

I will break this sum into two smaller ones: S 1 S_{1} and S 2 S_{2} , such that:

{ S 1 = i = 0 2 i 2 i S 2 = i = 0 1 2 i \begin{cases} S_{1} = \displaystyle \sum_{i=0}^\infty \frac{2i}{2^{i}} \\ S_{2} = \displaystyle \sum_{i=0}^\infty \frac{1}{2^{i}} \end{cases}

First, notice that S 2 S_{2} is an infinite geometric series with first term equal to 1 and ratio 1 2 \frac{1}{2} ; thus, its value equals 1 1 1 2 = 2 \frac{1}{1 - \frac{1}{2}} = 2 .

Now, let's work with S 1 S_{1} .

S 1 = i = 0 2 i 2 i = i = 0 i 2 i 1 S_{1} = \displaystyle \sum_{i=0}^\infty \frac{2i}{2^{i}} = \displaystyle \sum_{i=0}^\infty \frac{i}{2^{i - 1}}

S 1 = 1 2 0 + 2 2 1 + 3 2 2 + + p 2 p 1 + S_{1} = \frac{1}{2^{0}} + \frac{2}{2^{1}} + \frac{3}{2^{2}} + \ldots + \frac{p}{2^{p - 1}} + \ldots

Multiplying both sides by two:

2 S 1 = 2 + 2 2 0 + 3 2 1 + + p + 1 2 p 1 + 2S_{1} = 2 + \frac{2}{2^{0}} + \frac{3}{2^{1}} + \ldots + \frac{p + 1}{2^{p - 1}} + \ldots

Subtracting S 1 S_{1} from 2 S 1 2S_{1} :

2 S 1 S 1 = 2 + 1 + 1 2 1 + 1 2 2 + + 1 2 p 1 + = 2 + i = 0 1 2 i = 2 + S 2 2S_{1} - S_{1} = 2 + 1 + \frac{1}{2^{1}} + \frac{1}{2^{2}} + \ldots + \frac{1}{2^{p - 1}} + \ldots = 2 + \displaystyle \sum_{i=0}^\infty \frac{1}{2^{i }} = 2 + S_{2}

Thus, S 1 = 2 + S 2 = 2 + 2 = 4 S_{1} = 2 + S_{2} = 2 + 2 = 4 , and therefore S = S 1 + S 2 = 2 + 4 = 6 S = S_{1} + S_{2} = 2 + 4 = 6 .

Even though it was lengthy, I really liked. It is very helpful for those who lack knowledge in series

Razik Ridzuan - 6 years, 3 months ago

Even though I know how to solve this using series, this was the first way I've learned to solve this question and I thought I'd share it with everyone else. Thanks for the compliment (=

Alexandre Miquilino - 6 years, 3 months ago

n = 0 x n = 1 1 x x 1 \sum_{n=0}^{ \infty } x^{n} = \dfrac{1}{1-x} \quad \forall \quad |x| \leq 1 n = 0 ( d d x x n ) = d d x ( 1 1 x ) n = 0 ( n x n ) = x ( 1 x ) 2 n = 0 d d x ( n x n ) = d d x ( x ( 1 x ) 2 ) n = 0 ( n 2 x n ) = x ( 1 x ) 2 + 2 x ( 1 x ) ( 1 x ) 4 = x + x 2 ( 1 x ) 3 \Rightarrow \sum_{n=0}^{ \infty } ( \frac{d}{dx} x^{n} ) = \frac{d}{dx} ( \dfrac{1}{1-x} ) \\ \Rightarrow \sum_{n=0}^{ \infty} ( n \cdot x^{n} ) = \dfrac{x}{ (1-x)^{2} } \\ \Rightarrow \sum_{n=0}^{ \infty} \frac{d}{dx} (n \cdot x^{n} ) = \frac{d}{dx} ( \dfrac{x}{ (1-x)^{2} } ) \\ \Rightarrow \sum_{n=0}^{ \infty} ( n^{2} \cdot x^{n} ) = x\cdot \dfrac{ (1-x)^{2} + 2x\cdot (1-x) }{ (1-x)^{4} } \\= \frac{x+x^{2}}{ (1-x)^{3} }

Well, we just input x = 1 2 x= \dfrac{1}{2} and we get the answer as 6 6 .

Joel Yip
Feb 20, 2015

n = 1 n 2 2 n = n = 0 ( n + 1 ) 2 2 n + 1 = 1 2 ( n = 0 ( n 2 2 n + 2 n 2 n + 1 2 n ) ) = 1 2 ( n = 0 n 2 2 n + 2 n = 0 n 2 n + n = 0 1 2 n ) = 1 2 ( n = 1 n 2 2 n + 0 + 2 ( 2 ) + 2 ) = 1 2 ( n = 1 n 2 2 n + 6 ) = 1 2 n = 1 n 2 2 n + 3 n = 1 n 2 2 n 1 2 n = 1 n 2 2 n = 3 1 2 n = 1 n 2 2 n = 3 n = 1 n 2 2 n = 6 \sum _{ n=1 }^{ \infty }{ \frac { { n }^{ 2 } }{ { 2 }^{ n } } } =\sum _{ n=0 }^{ \infty }{ \frac { { (n+1) }^{ 2 } }{ { 2 }^{ n+1 } } } \\ \qquad \qquad =\frac { 1 }{ 2 } \left( \sum _{ n=0 }^{ \infty }{ \left( \frac { { n }^{ 2 } }{ { 2 }^{ n } } +2\frac { { n } }{ { 2 }^{ n } } +\frac { 1 }{ { 2 }^{ n } } \right) } \right) \\ \qquad \qquad =\frac { 1 }{ 2 } \left( \sum _{ n=0 }^{ \infty }{ \frac { { n }^{ 2 } }{ { 2 }^{ n } } } +2\sum _{ n=0 }^{ \infty }{ \frac { { n } }{ { 2 }^{ n } } } +\sum _{ n=0 }^{ \infty }{ \frac { 1 }{ { 2 }^{ n } } } \right) \\ \qquad \qquad =\frac { 1 }{ 2 } \left( \sum _{ n=1 }^{ \infty }{ \frac { { n }^{ 2 } }{ { 2 }^{ n } } } +0+2(2)+2 \right) \\ \qquad \qquad =\frac { 1 }{ 2 } \left( \sum _{ n=1 }^{ \infty }{ \frac { { n }^{ 2 } }{ { 2 }^{ n } } } +6 \right) \\ \qquad \qquad =\frac { 1 }{ 2 } \sum _{ n=1 }^{ \infty }{ \frac { { n }^{ 2 } }{ { 2 }^{ n } } } +3\\ \sum _{ n=1 }^{ \infty }{ \frac { { n }^{ 2 } }{ { 2 }^{ n } } } -\frac { 1 }{ 2 } \sum _{ n=1 }^{ \infty }{ \frac { { n }^{ 2 } }{ { 2 }^{ n } } } =3\\ \\ \frac { 1 }{ 2 } \sum _{ n=1 }^{ \infty }{ \frac { { n }^{ 2 } }{ { 2 }^{ n } } } =3\\ \sum _{ n=1 }^{ \infty }{ \frac { { n }^{ 2 } }{ { 2 }^{ n } } } =6\\

Hi @joel yip , I think that maybe you should add how you got 0 n 2 n = 2 \sum_{0}^{\infty} \dfrac{n}{2^{n}} = 2 to make your answer complete .

Well, it's just a suggestion ¨ \ddot\smile

EDIT * I have added my own solution .

A Former Brilliant Member - 6 years, 3 months ago

Thanks for the suggestion but I got it from a book called "The Pleasures of Pi,e".

Joel Yip - 6 years, 3 months ago

Yes, I am also curious to know how did you conclude m = 0 n 2 n = 2 \sum_{m=0}^{\infty}\frac{n}{2^n} = 2 ?

Janardhanan Sivaramakrishnan - 6 years, 3 months ago

Sir, you'll get your answer if you put x = 1 2 x=\frac{1}{2} in the step preceding the step where I differentiate for the second time , in my solution .

A Former Brilliant Member - 6 years, 3 months ago

Its an arithmetico geometrico progression you can solve it by taking it as S and multiply the common ratio to it and subtract from S to get a GP then you can solve it

Shanthan Kumar - 6 years, 3 months ago

could you explain me the conversion from third to fourth step .how can summation be changed to 1 again ????

Shehanaaz Sk - 6 years, 3 months ago

What Joel did is actually the following

n = 0 n 2 2 n = 0 2 0 + n = 1 n 2 2 n \sum_{n=0}^{\infty} \dfrac{n^{2}}{2^{n}} = \dfrac{0}{2^{0}} + \sum_{n=1}^{\infty} \dfrac{n^{2}}{2^{n}}

Maybe this will clear your doubt :)

A Former Brilliant Member - 6 years, 3 months ago
Brock Brown
Feb 20, 2015

Python:

1
2
3
4
5
6
7
8
from fractions import Fraction as frac
n = 1
infinity = 1000
total = 0
while n <= infinity:
    total += frac(n*n, 2**n)
    n += 1
print "Answer:", float(total)

Moderator note:

This solution has been marked wrong. You have only calculated the value of n = 1 1000 n 2 2 n \sum_{n=1}^{1000} \frac {n^2}{2^n} instead of the series in question.

One can use the notion of generating functions to conclude as in Azhaghu Roopesh M's solution.

Mohammed Hssein - 6 years, 3 months ago

Can you assume infinity =1000?????

Joel Yip - 6 years, 3 months ago

You can assume infinity is 1000 to get a good answer, and you can make infinity bigger (let's say infinity is 2000) to get a better answer.

Brock Brown - 6 years, 3 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...